Is there such a thing as too long childcare leave?. Issue 1 (14th March 2017) - Nieuwenhuis, Rense; Need, Ariana; Van der Kolk, Henk
Abstract : Purpose: The purpose of this paper is to revisit the question whether women's employment is negatively affected in countries with very long periods of childcare leave. Design/methodology/approach: The authors analyzed data on 192, 484 individual women, 305 country-years, and 18-countries, combined with country-level data on childcare, unemployment and service sector size. Findings: The authors found that in countries with short periods of childcare leave the motherhood-employment gap is smaller than in countries with no childcare leave, while in countries with long periods of childcare leave the motherhood-employment gap is bigger than with short periods of leave. Originality/value: The authors argued that to correctly answer the long-leave question – the relationship between duration of leave and employment of women should be explicitly hypothesized as being curvilinear; and childcare leave should be expected to affect only mothers, not women without children; testing the long-leave hypothesis requires the use of country-comparative data in which countries are observed repeatedly over time; and is best tested against person-level data.